The upper frequency limit for the use of phase locking to code temporal fine structure in humans: A compilation of viewpoints - Verschooten, Eric (Hear Res, 2019)
The relative importance of neural temporal and place coding in auditory perception is still a matter of much debate. The current article is a compilation of viewpoints from leading auditory psychophysicists and physiologists regarding the upper frequency limit for the use of neural phase locking to code temporal fine structure in humans. While phase locking is used for binaural processing up to about 1500 Hz, there is disagreement regarding the use of monaural phase-locking information at higher frequencies. Estimates of the general upper limit proposed by the contributors range from 1500 to 10000 Hz. The arguments depend on whether or not phase locking is needed to explain psychophysical discrimination performance at frequencies above 1500 Hz, and whether or not the phase-locked neural representation is sufficiently robust at these frequencies to provide useable information. The contributors suggest key experiments that may help to resolve this issue, and experimental findings that may cause them to change their minds. This issue is of crucial importance to our understanding of the neural basis of auditory perception in general, and of pitch perception in particular.